Academic Management Innovation of Islamic Private Schools Based on the Concept of Muslim Youth Characteristics for Future Global Society - Assomadee, Muhammad (Journal of Islamic Studies, Prince of Songkla University, 2025)
Objectives: This research aims to develop innovations in academic administration of private Islamic schools according to the concept of characteristics of Muslim youth for a future world society. Methodology: it used a multi-phase mixed methods research, divided into 3 phases. The sample group were: Private Islamic schools in the three southern border provinces, a total of 111 schools. The tools used in the research were 1) assessment forms, 2) questionnaires, and 3) interviews. Data were analyzed by calculating 1) frequency, 2) mean, and 3) standard deviation. 4. necessity confirmatory factor analysis and 5) content analysis. Research Findings: The results of the research found that academic administration innovation is to enhance the characteristics of Muslim youth for the future global society. It consists of 3 sub-innovations: (1) Innovation in developing a curriculum to enhance the characteristics of Muslim youth for a future global society in learning, thinking, and adapting. 2) Innovation in teaching and learning to enhance the characteristics of Muslim youth for a future global society in thinking, adapting, and learning. (3) Innovation in measurement and evaluation to enhance the characteristics of Muslim youth for a future global society in thinking and learning. Contributions: Policy-level agencies in the area or educational administrators in the network of private Islamic schools should give importance to applying research results to school administration policy determination in order to develop learners with Muslim youth characteristics for the future global society.